2021
DOI: 10.3390/vaccines9090973
|View full text |Cite
|
Sign up to set email alerts
|

Counties with Lower Insurance Coverage and Housing Problems Are Associated with Both Slower Vaccine Rollout and Higher COVID-19 Incidence

Abstract: Equitable vaccination distribution is a priority for outcompeting the transmission of COVID-19. Here, the impact of demographic, socioeconomic, and environmental factors on county-level vaccination rates and COVID-19 incidence changes is assessed. In particular, using data from 3142 US counties with over 328 million individuals, correlations were computed between cumulative vaccination rate and change in COVID-19 incidence from 1 December 2020 to 6 June 2021, with 44 different demographic, environmental, and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
2
18
0
1
Order By: Relevance
“…Demographic and social characteristics factors at the micro level were among the most frequent components affecting the distribution of Covid-19 vaccine. For example, according to some studies in the United States and the United Kingdom [ 39 , 49 ], the rate of vaccine injection is higher in women than men. Also, older people had greater access to vaccination [ 34 , 36 , 39 , 40 , 42 , 44 , 48 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Demographic and social characteristics factors at the micro level were among the most frequent components affecting the distribution of Covid-19 vaccine. For example, according to some studies in the United States and the United Kingdom [ 39 , 49 ], the rate of vaccine injection is higher in women than men. Also, older people had greater access to vaccination [ 34 , 36 , 39 , 40 , 42 , 44 , 48 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, according to some studies in the United States and the United Kingdom [ 39 , 49 ], the rate of vaccine injection is higher in women than men. Also, older people had greater access to vaccination [ 34 , 36 , 39 , 40 , 42 , 44 , 48 , 50 , 51 ]. A study by Cardona et al in Maryland found that vaccination rates were lower in blacks [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ref. [22] analyzes the influence of poverty and other socio-economic factors on the vaccination rate, with the study's results showing that negative socio-economic indicators, such as a lack of insurance, firearm fatalities, and housing problems, have a significantly negative influence on the vaccination rate.…”
Section: Discussionmentioning
confidence: 99%